Compression Wraps—Providing Solutions for Complex Lymphatic Presentations. - Witt, Susan; González Rubino, Jesús Baltasar; Martín-Valero, Rocío; Viñolo-Gil, Maria Jesús; Dieterle, Thomas (MDPI, 2024)
Compression is the cornerstone of treatment for lymphoedema; however, in patients with Stage III lymphoedema that causes a significant alteration of limb shape and size, additional creative problem solving is required in order to find a solution that fits the person, their limb and their personal circumstances. Medical adaptive compression (MAC) systems provide solutions to complex situations. We present two cases of individuals who completed an inpatient rehabilitation stay for intensive treatment of their lymphoedema and were fitted with MAC devices to ensure long-term success.
Keywords: Linfedema; Lymphedema; Rehabilitation; Compression stocking; Compression wrap; Medical adaptive compression devices